Therapeutic effect of small extracellular vesicles from cytokine-induced memory-like natural killer cells on solid tumors - Shi, Yinghong; Chen, Yanxia; Wang, Yi; Mo, Dan; Ai, Huisheng; Zhang, Jianguo; Guo, Mei; Qian, Hui (Journal of nanobiotechnology, 2024)
Small extracellular vesicles (sEV) derived from diverse natural killer (NK) cell lines have proven their exceptional antitumor activities. However, sEV from human primary NK cells, especially memory-like NK cells, are rarely utilized for cancer treatment. In this study, we obtained sEV from IL-12, IL-15 and IL-18 cultured human memory-like NK cells (mNK-sEV) that showed strong cytokine-secretory ability. It was uncovered that mNK-sEV entered cancer cells via macropinocytosis and induced cell apoptosis via caspase-dependent pathway. Compared to sEV from conventionally cultured NK cells (conNK-sEV), mNK-sEV inhibited tumor growth to a greater extent. Concomitantly, pharmacokinetics and biodistribution results validated a higher accumulation of mNK-sEV than conNK-sEV in tumors of xenografted murine models. Notably, elevated containment of granulysin (GNLY) within mNK-sEV, at least in part, may contribute to the enhanced therapeutic effect. Herein our results present that mNK-sEV can be a novel class of therapeutic reagent for effective cancer treatment.